Scientific cane cultivation gave fame and name: A tale of a cane Entrepreneur - Singh, B P; Pandey, Rakesh; Chander, Mahesh; Pordhiya, Kishore Kumar; Shriram, Santosh (Indian Farming, 2020)
SUGARCANE as leading cash crop led India a second largest producer of sugar (17.1%) in the world after Brazil. Within India, Uttar Pradesh (36.1%), Maharashtra (34.3%) and Karnataka (11.7%) are the three largest cane producers. Although, area under cane has decreased, viz. 50.66, 49.27 and 43.89 lakhs ha during 2014-15, 2015-16, and 2016-17, respectively, but the production and yield were in increasing order (362.33 348.45 306.72 million tonnes sugarcane production and yield 71512, 70720 and 69886 kg/ha) during the same period. Further, the sugar production has also increased to 32.25 million tonnes in 2017-18 in comparison to the 24.8 million tonnes produced in 2015-16 attributed by the availability and accessibility of farmers to superior seeds of cane, modern cultivation practices and other essential inputs.